Phase Locked Loop System with SIW-based Bandpass Filter for D-band Microwave Interferometer. Issue 1 (2nd January 2022) - Vala, Alpesh; Patel, Amit; Patel, Bhargav; Sinha, Abhishek; Nagora, Umesh; Pathak, Surya; Chaudhari, Jitendra; Mewada, Hiren
Abstract : This paper presents the development and implementation of a low phase-noise stable signal generator for a D-band microwave interferometer application used in the fusion plasma diagnostics. A phase locked loop (PLL) circuit is designed to generate the stable frequencies of 2.3 and 2.333 GHz which is then up-converted to 6.9 GHz and 7 GHz as required by the interferometer system. Programmable synthesizer with temperature compensated crystal oscillator (TCXO) is used to develop the PLL. In order to remove the higher order harmonics generated from the system, a substrate integrated waveguide (SIW) based bandpass filter is proposed which offers a low insertion loss with compact size. The proposed bandpass filter is designed and simulated in high-frequency structure simulator (HFSS) software. The bandpass filter provides pass band for frequencies ranging from 6.8 GHz to 7.2 GHz with an insertion loss of 0.5 dB and a return loss more than 25 dB. ADsim PLL software is used to derive PLL parameters and Altium software is used for the printed circuit board (PCB) design. Measured results are in consensus with the requirement of the interferometer system.